Introduction to Special Issue: New Developments in Public Defense Research. (July 2020) - Moore, Janet; Davies, Andrew L. B.
This special issue focuses on interdisciplinary research in public defense. Seven papers represent a diverse group of scholars in an understudied field. Two overarching themes emerge. The first theme, "System Interventions: Evaluating Programs and Identifying Opportunities, " includes three studies of innovative policies and practices. Two evaluate new resource injections that support, respectively, social work-initiated holistic defense and counsel at first appearance. The third examines state sentencing schemes to identify opportunities for emphasizing defendant assets instead of deficits. The second theme, "Understanding Decision Makers, " includes four papers drawing on qualitative data regarding juvenile resentencing and reentry, defendant views of attorney–client communication, defender motivations for remaining in the profession, and manager perspectives on likely effects of caseload reductions. As a collection, these papers bridge gaps between theory and practice, offer new insight into public defense as a critical component of criminal legal systems, and identify new avenues for future research.